Comparative epidemiological analysis of maternal mortality ratios in Brazil and Santa Catarina between 2012 and 2022 (Research, Society and Development, 2025)
Maternal mortality remains a serious public health problem, especially in developing countries. This study aimed to compare the Maternal Mortality Ratio (MMR) between Brazil and the state of Santa Catarina from 2012 to 2022, as well as to analyze the epidemiological profile of maternal deaths in Santa Catarina. This is an ecological, descriptive, and retrospective study based on secondary data obtained from SIM and SINASC, analyzed using descriptive statistics. During the analyzed period, Brazil presented an MMR of 62.94, while Santa Catarina recorded 36.94. The year 2021 showed the highest MMR in both contexts, coinciding with the COVID-19 pandemic. In Santa Catarina, most deaths occurred in women aged 30 to 39 years, white, with 8 to 11 years of education, and single. The main cause of death was direct obstetric causes, with most occurring in the postpartum period up to 42 days. The macro-regions with the highest number of deaths were Planalto Norte and Nordeste. The results suggest that although Santa Catarina shows rates below the national average, maternal mortality remains significant, especially in contexts of social vulnerability and during health crises. It is concluded that effective public policies and continuous monitoring of prenatal, childbirth, and postpartum care are essential to reduce preventable deaths.